Restaurant servers' risk perceptions and risk communication-related behaviors when serving customers with food allergies in the U.S. (July 2017) - Wen, Han; Kwon, Junehee
Abstract: Communication between and among customers with food allergies and foodservice staff has become a concern in the restaurant industry. The purpose of this research was to explore the perceived risks and risk communication-related behaviors of restaurant servers when serving customers with food allergies in the U.S. An online survey instrument was developed based on interviews with full service restaurant managers, pilot-tested, and distributed through an online survey research firm. The results indicated that most servers lacked knowledge about food allergies and perceived that initiating communication and preventing allergic reactions were mostly the responsibilities of customers with food allergies. Servers' risk reduction and communication behaviors were affected by their perceived severity of food allergy reactions, previous training, sources of media exposure, and the perceived responsibilities of preventing food allergy reactions. Restaurateurs and foodservice educators may use these findings to develop training and strategies for food allergy risk communication in the restaurant industry.